Answer:
f^-1(x) = (x-1)/-3
Step-by-step explanation:
Invert equation:
Describe X in original function:
multiplied by -3
add 1
Reverse order:
subtract 1
divide by -3
You have y-4 = (x-8)
Add 4 to each side:
Y = (x-8) +4
Remove the parenthesis and combine like terms to get:
y = x-4
43.3% All you need to do is move the decimal two places to the right and there you go.
Im not exactly sure but i think its about 12 inches
Answer:(D) is the answer
Step-by-step explanation:
for every cup grandma uses 3/4 of a cup of strawberry